Makna Modal Kerja dalam Perspektif Budaya Bagi Pedagang Sapi di Pasar Balongpanggang - Altiana Altiana; Rahmat Agus Santoso (Jurnal Mirai Management, 2022)
Abstract This study aims to determine the meaning of working capital in a cultural perspective for cattle traders in Balongpanggang District, because cattle traders in the market only sell on Thursdays. and conduct sale and purchase agreements between traders and buyers. This type of research is qualitative research with data collection techniques through observation and interviews. The object of this research is the animal market in the Balongpanggang District. The results of this study indicate that the meaning of working capital in a cultural perspective is the application of cultural norms which means not obtaining working capital from something that is prohibited. The working capital of the cattle traders comes from their own capital and borrowed capital from family or friends by entering into ewuh pakewuh agreements that do not violate cultural norms and values. a custom that has been going on since ancient times which is carried out every Thursday to make sales because it is considered a good day and makes the sale and purchases agreement an added value between the seller and the buyer regarding the suitability of the animal and the object of the contract. Keywords: working capital, culture, sale and purchase contract